Clinical supervisors and cultural competence. (August 2014) - Berger, Gabriella; Conroy, Sheree; Peerson, Anita; Brazil, Victoria
Summary Objective To investigate how clinical supervisors of junior doctors provide feedback and assessment on cultural competence, one of several professionalism skills outlined in the Australian Curriculum Framework for Junior Doctors. Methods Twenty clinical supervisors were recruited to a qualitative study in a regional hospital in Queensland, Australia. Data from semi‐structured interviews (June–August 2011) were thematically analysed. Results Interviews revealed that cultural competence was interpreted by the supervising clinicians as a vague concept, and that junior doctors were not assessed in this area. Additional themes related to the cultural competence of junior doctors, as reported by their supervisors, included: limited direct supervision of, and feedback to, junior doctors; variations in approaches to assessment; clinicians' communication focuses on clinical aspects of disease process; perceived lack of cultural diversity among staff and patients; acceptance of laypersons as English interpreters; language barriers with international medical graduates; and patients' low levels of health literacy. Conclusion Supervisors were unable to define cultural competence in ways that enable them to apply the concept to clinical training for junior doctors. Specific training in cultural competence, and guidelines for its assessment, is therefore recommended for clinical supervisors and junior doctors to improve their approaches to patient care and health outcomes.